Effectiveness of plasters and textile reinforced mortars for strengthening clay masonry infill walls subjected to combined in‐plane/out‐of‐plane actions / Wirksamkeit von Putz und textilbewehrtem Mörtel bei der Verstärkung von Ausfachungswänden aus Ziegelmauerwerk, die kombinierter Scheiben‐ und Plattenbeanspruchung ausgesetzt sind. Issue 5 (October 2015) - da Porto, Francesca; Guidi, Giovanni; Verlato, Nicolò; Modena, Claudio
Abstract This work presents the results of experimental tests on full‐scale one‐bay, one‐storey reinforced concrete (RC) frames, filled with non‐load‐bearing clay masonry walls. The infill walls were made with clay masonry units characterized by a high percentage of voids and low strength. Such 'light' infill walls have shown fragile behaviour during recent earthquakes, due to the combined effects of damage produced by out‐of‐plane seismic action, together with in‐plane deformation of the RC frame. In this context, various solutions to the problems involved in external reinforcement of 'light' infill walls, typically found in existing RC buildings but still used in common construction practice, have recently been developed. These solutions are: i) special lime‐based plaster with geo‐polymer binder; ii) bidirectional composite meshes applied with inorganic matrices, i.e., Textile Reinforced Mortars (TRM); iii) TRM improved by anchorage of the mesh to the RC frame. For these construction elements, a special set‐up for combined in‐plane/out‐of‐plane cyclic testing, already used for other infill wall types at the University of Padova, was used. In particular, this work describes: a) materials and systems for strengthening infill walls; b) experimental results of infill walls under in‐plane loads; c) effects of out‐of‐plane loads on previously in‐plane damaged infill walls. The final aim was to achieve complete mechanical characterization of infill walls in both original and strengthened conditions, and to validate the effectiveness of the proposed strengthening systems.